Enterobius vermicularis in the Appendiceal Lumen: A Case Report - Mehta Razzaghi; Hosna Rezaei; Farshid Mohammadi; Amir Mohammad Salehi (Case Reports in Surgery)
Enterobius vermicularis is a common parasitic infection worldwide. Acute appendicitis (AA) is a frequently encountered condition in general surgery; however, its association with E. vermicularis remains controversial. AA caused by E. vermicularis is a relatively uncommon infection that primarily affects children. We reported a 21-year-old female who was admitted to our hospital due to right lower quadrant abdominal tenderness. Laboratory tests and imaging were not consistent with AA. She underwent a diagnostic laparoscopy and appendectomy. Histopathological examinations revealed the presence of E. vermicularis in the lumen of the appendix, which caused its obstruction without evidence of inflammatory cell infiltration or lymphoid hyperplasia.